Effects of Simulated Space Radiations on the Tomato Root Proteome - Desiderio, Angiola; Salzano, Anna Maria; Scaloni, Andrea; Massa, Silvia; Pimpinella, Maria; De Coste, Vanessa; Pioli, Claudio; Nardi, Luca; Benvenuto, Eugenio; Villani, Maria Elena (Frontiers in Plant Science, 2019)
Plant cultivation on spacecraft or planetary outposts is a promising and actual perspective both for food and bioactive molecules production. To this aim, plant response to ionizing radiations, as an important component of space radiation, must be assessed through on-ground experiments due to the potentially fatal effects on living systems. Hereby, we investigated the effects of X-rays and γ-rays exposure on tomato “hairy root” cultures (HRCs), which represent a solid platform for the production of pharmaceutically relevant molecules, including metabolites and recombinant proteins. In a space application perspective, we used an HRC system previously fortified through the accumulation of anthocyanins, which are known for their anti-oxidant properties. Roots were independently exposed to different photon radiations, namely X-rays (250 kV) and γ-rays (Co60, 1.25 MeV), both at the absorbed dose levels of 0.5, 5, and 10 Gy. Molecular changes induced in the proteome of HRCs were investigated by a comparative approach based on two-dimensional difference in-gel electrophoresis (2D-DIGE) technology, which allowed to highlight dynamic processes activated by these environmental stresses. Results revealed a comparable response to both photon treatments. In particular, the presence of differentially represented proteins were observed only when roots were exposed to 5 or 10 Gy of X-rays or γ-rays, while no variations were appreciated at 0.5 Gy of both radiations, when compared with unexposed control. Differentially represented proteins were identified by mass spectrometry procedures and their functional interactions were analyzed, revealing variations in the activation of stress response integrated mechanisms as well as in carbon/energy and protein metabolism. Specific results from above-mentioned procedures were validated by immunoblotting. Finally, a morphometric analysis verified the absence of significant alterations in the development of HRCs, allowing to ascribe the observed variations of protein expression to processes of acclimation to ionizing radiations. Overall results contribute to a meaningful risk evaluation for biological systems exposed to extra-terrestrial environments, in the perspective of manned interplanetary missions planned for the near future.